Effects of Stitch Length on Wound Complications After Closure of Incision - Jalanee , Rizwan; Choudhary , Muhammad Amjad; Arif, Khurram; Khan , Irfanullah; Muhammad Hussain; Kakar , Sana Ullah (Indus Journal of Bioscience Research, 2025)
Background: Surgical incision closure is essential for wound healing and postoperative recovery. Stitch length plays a critical role in preventing complications such as infection, dehiscence, and delayed healing. Optimal stitch length ensures tissue approximation without excessive tension, yet its precise impact on wound complications remains unclear. Objective: This study aims to evaluate the effects of different stitch lengths on wound complications after surgical incision closure, with a focus on surgical site infections (SSIs), incisional hernias, and delayed healing. The goal is to identify optimal suture techniques for better postoperative outcomes. Methods: A comparative study was conducted at a tertiary care hospital Pakistan Institute of Medical Sciences PIMS, involving 200 patients who underwent midline incision closure with either long or short stitch lengths. Data were collected through patient interviews, direct observations, and medical record reviews. Wound complications and recovery parameters were analyzed to identify significant patterns and risk factors. Results: The study found significantly higher rates of wound complications, including superficial and deep infections, wound dehiscence, and incisional hernias in the long stitch group compared to the short stitch group. Shorter stitch lengths resulted in a higher SL to WL ratio and fewer complications. Conclusion: Shorter stitch lengths with a higher SL to WL ratio reduce the incidence of wound complications following surgical incision closure. These findings suggest that adopting shorter stitch lengths may improve patient recovery and minimize healthcare costs associated with postoperative complications.